Experimental study in a spray filled tower for flow visualization and drift eliminators characteristics - Mohiuddin, A. K. M. (Asian Network for Scientific Information, 2005)
This study demonstrates the result of an experiment in a spray filled forced draft cooling tower. Air distribution at some specific points within the tower was investigated. The pressure drop and drift loss characteristics of cellular type drift eliminators and those made of wood and cement-asbestos were also experimentally investigated. The experiments were conducted with one, two and three stages of cellular type drift eliminators and that for wooden and cement-asbestos drift eliminators with two and three stages only with various orientation angle, • of the eliminator plates. The results showed that the pressure drop and drift loss were strong functions of number of stages, n and air flow rate. In case of wooden and cement-asbestos drift eliminators, pressure drop and drift loss were strongly dependent on • as well. For various flow rates of the air, the flow patterns inside the tower were found similar. The study establishes the superiority of the cellular type drift eliminators over the others.